The cardioprotection granted by metoprolol is restricted to its administration prior to coronary reperfusion - Ibanez, Borja (2009)
BACKGROUND: Myocardial infarct size is a strong predictor of cardiovascular events. Intravenous metoprolol before coronary reperfusion has been shown to reduce infarct size; however, it is unknown whether oral metoprolol initiated early after reperfusion, as clinical guidelines recommend, is similarly cardioprotective. We compared the extent of myocardial salvage associated with intravenous pre-reperfusion-metoprolol administration in comparison with oral post-reperfusion-metoprolol or placebo. We also studied the effect on suspected markers of reperfusion injury. METHODS: Thirty Yorkshire-pigs underwent a reperfused myocardial infarction, being randomized to pre-reperfusion-metoprolol, post-reperfusion-metoprolol or placebo. Cardiac magnetic resonance imaging was performed in eighteen pigs at day 3 for the quantification of salvaged myocardium. The amounts of at-risk and infarcted myocardium were quantified using T2-weighted and post-contrast delayed enhancement imaging, respectively. Twelve animals were sacrificed after 24 h for reperfusion injury analysis. RESULTS: The pre-reperfusion-metoprolol group had significantly larger salvaged myocardium than the post-reperfusion-metoprolol or the placebo groups (31±4%, 13±6%, and 7±3% of myocardium at-risk respectively). Post-mortem analyses suggest lesser myocardial reperfusion injury in the pre-reperfusion-metoprolol in comparison with the other 2 groups (lower neutrophil infiltration, decreased myocardial apoptosis, and higher activation of the salvage-kinase phospho-Akt). Salvaged myocardium and reperfusion injury pair wise comparisons proved there were significant differences between the pre-reperfusion-metoprolol and the other 2 groups, but not among the latter two. CONCLUSIONS: The intravenous administration of metoprolol before coronary reperfusion results in larger myocardial salvage than its oral administration initiated early after reperfusion. If confirmed in the clinical setting, the timing and route of β-blocker initiation could be revisited.